Respon Investor Asing Terhadap Risiko Ekonomi Indonesia - M. Rasyidin; Maryana; M. Saleh; Nova; Zulfikar (Forum Kerjasama Pendidikan Tinggi, 2023)
This study aims to examine the response of foreign investors to economic risk. Economic risk is measured using inflation rate, interest rate and exchange rate. This research uses a quantitative approach method. The data used is monthly data for 3 years starting from January 2021 to December 2022. The Quantitative data used in the form of foreign investment data, inflation, interest rates and exchange rates for 36 months. The data analysis method used is multiple linear regression analysis. The results showed that investors responded positively to economic risks such as inflation, interest rates and exchange rates but only inflation variables were responded significantly by foreign investors. It is expected that with these findings, the government can take policies to stabilize inflation in Indonesia, given the positive response of investors to this economic risk. By stabilizing inflation, interest rates will also be under control, as well as the government maintaining the stability of the Rupiah exchange rate by managing the supply and demand of foreign exchange and maintaining rupiah liquidity.